ORGANIZATION OF CONTINUOUS SPIRITUAL EDUCATION IN HIGHER EDUCATION INSTITUTIONS - Alisherova Madinabonu Marksovna (Scholars Digest Publishing, 2023)
This article discusses the formation of uninterrupted moral education in higher education institutions.
Keywords: Spirituality, upbringing, concept, strategy, tactics, qualification staff, pedagogical.